Consumo de chimarrão em mulheres diagnosticadas com câncer de mama: correlação clinico-patológica e associação com níveis circulantes de cafeína e antioxidantes - Calixto, Maria Rachel Pedrazzoli (2019)
Introduction: Breast cancer is the second most common malignant neoplasm among women, presenting high clinical and biological heterogeneity, leading to a complex disease. Both internal and external factors are determinant for the disease prevention and progression. Ilex paraguariensis A. St. Hil, a specimen of significant interest in ethnopharmacology, consumed in Southern Brazil mainly in the form of chimarrão, displays a complex chemical composition and is rich in antioxidants potentially exploited in several studies, in addition to acting in the prevention of diseases caused by oxidative stress, such as cancer. This study aims to investigate the clinico-pathological outcome of breast cancer women chimarrão consumers compared to non-consumers. Methodology: A total of 199 women treated at the Francisco Beltrão Cancer Hospital (Ceonc) were volunteers from May 2015 to December 2017 presenting suspected breast cancer lesions . All women with benign breast disease were excluded, totaling a group of 79 women presenting breast cancer who presented all the clinico-pathological data for inclusion in the study. Chimarrão consumption was categorized as positive or negative, the antioxidant profile was evaluated through the determination of reduced glutathione and metallothionein contents and catalase activity, in addition to caffeine blood level. Results and Discussion: Decreases in reduced Glutathione and metallothignein levels and increases in catalase activity were observed among chimarrão consumers. The levels of circulating caffeine in patients with molecular Luminal A subtype were higher in comparison to Luminal B and subtype HER-2, whereas concerning the distribution agreement with body mass index (BMI), those overweight presented higher caffeine levels than the obese women compared to eutrophic ones.